Copolymers of 4‐thieno[3, 2‐b]thiophen‐3‐ylbenzonitrile with anthracene and biphenyl; synthesis, characterization, electronic, optical, and thermal properties. Issue 1 (8th December 2020) - Isci, Recep; Gunturkun, Dilara; Yalin, Ahsen Sare; Ozturk, Turan
Abstract: Two novel copolymers of 4‐thieno[3, 2‐ b ]thiophen‐3‐ylbenzonitrile (TT‐CN), possessing electron withdrawing cyano moiety, with anthracene (P1) and biphenyl (P2) were prepared via Suzuki coupling. Optic, electronic, and thermal properties of the copolymers were investigated through UV–Vis spectroscopy, cyclic voltammetry, gel permeation chromatography, and thermal gravimetric analysis. The polymers with anthracene and biphenyl had electronic band gaps of 2.01 and 1.90 eV, respectively. Both polymers demonstrated excellent large Stokes shifts of 101 (anthracene) and 105 nm (biphenyl) as well as very good thermal properties. As they had good optical, electronic, and thermal properties, they are promising candidates for electronic applications. Abstract : Copolymers of 4‐thieno[3, 2‐ b ]thiophen‐3‐ylbenzonitrile, having electron withdrawing cyano substituent, with rigid anthracene and biphenyl units, were synthesized by successive Palladium (0) catalyzed Suzuki polymerization. Their electronic and optical properties were investigated by UV–Vis spectroscopy, fluorescence spectroscopy, CV, and solvatochromic studies with different solvents. They demonstrated to be good candidates for electronic applications.